Profitability of alley farming with and without fallow in southwest Nigeria - Jabbar, M.A.; Larbi, Asamoah; Reynolds, L. (Cambridge University Press, 1994)
The profitabilities of three land use systems in the humid zone of southwest Nigeria are compared using a capital budgeting procedure combining on-station and on-farm experimental data. The systems are: non-alley farming with fallow; alley farming with fallow; and continous alley farming. The results indicate that: continous alley cropping is more profitable than non-alley or alley cropping with fallow; short fallowing in alley cropping reduces the rate of mining soil fertility and thus helps preserve future productivity; alley farming with small ruminants enhances the profitability of alley systems and increases their advantage over the non-alley system; and alley systems remain profitable even when terminal clearing costs are internalized in the current project cycle.